The mTOR Deficiency in Monocytic Myeloid-Derived Suppressor Cells Protects Mouse Cardiac Allografts by Inducing Allograft Tolerance - Li, Jiawei; Chen, Juntao; Zhang, Mingnan; Zhang, Chao; Wu, Renyan; Yang, Tianying; Qiu, Yue; Liu, Jingjing; Zhu, Tongyu; Zhang, Yi; Rong, Ruiming (Frontiers in Immunology, 2021)
Background: Myeloid-derived suppressor cells (MDSCs) could prevent allograft rejections and induce immune tolerance in transplantation models. Previous studies demonstrated that inhibition of mTOR signal could enhance MDSCs protective effect in cardiac transplantation model via promoting MDSCs expansion. And the inhibition of mTOR is related with autophagy. Herein, this study was designed to investigate the protective mechanism of mTOR deficiency M-MDSCs in cardiac transplantation model. Methods: Myeloid-specific mTOR conditional knockout mice were generated to get mTOR deficiency M-MDSCs. The proliferation and immunosuppressive function of mTOR deficiency M-MDSCs were determined by flow cytometry and CFSE T cell proliferation assays. mTOR deficiency M-MDSCs intracellular autophagy levels were determined by western blot and Electron microscopy. RNAseq analysis was performed for WT and mTOR-deficient M-MDSC cells. Cervical cardiac transplantation model mice were generated. ELISA were performed for control mice, model mice, WT MDSCs infusion model mice and mTOR-deficient MDSCs infusion model mice to examine the inflammatory cytokines in the recipients mice serum. Flow cytometry and immunohistochemistry were performed to determine mTOR-deficient MDSCs induced immune tolerance. Results: mTOR deficiency could promote M-MDSCs differentiation and enhance intracellular autophagy levels in vivo and in vitro. mTOR deficiency also enhance the immunosuppressive function of M-MDSCs. In addition, infusing mTOR deficiency M-MDSCs could also prolong cardiac allograft survival and establish immune tolerance in recipient mice by inhibiting T cell activation and inducing Tregs. Conclusion: mTOR-deficiency enhances M-MDSCs cells autophagy and immunosuppressive function and prolongs mice cardiac allograft survival.